Gwarancja prawa do opieki dyplomatycznej i konsularnej jako element instytucji obywatelstwa Unii Europejskiej - Kozłowski, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Diplomatic and consular protection is exceptional. It is an institution that ensures adequate protection of the legal interests of an individual. This often happens in extreme circumstances related to the presence of a person outside the home country and under the jurisdiction of a foreign state. EU treaties have extended the scope of this protection and oblige Member States to provide citizens of other EU countries with protection. The right provided for in primary law is one of the most important parts of EU citizenship institutions. This study is an attempt to highlight several problems related to the right to care provided by foreign services of EU Member States related to EU citizenship.
Keywords: the European Union; national citizenship; EU citizenship; diplomatic protection; consular protection